Investigation of MAl2−xSixO4−xNx:Eu2+ phosphor for improving luminescence properties of white LEDs - Thanh Binh Ly; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
We implement a solid-state reaction technique to make MAl2−xSixO4−xNx (M = Ca, Sr, Ba) as well as its variant doped with Eu at 1300 – 1400°C in a nitrogen hydrogen environment. Then, we measure the solubility of (SiN)+ in MAl2O4. By replacing (AlO)+ with (SiN)+, whose solubility is dependent on M cations, nitrogen may be integrated into MAl2O4. (SiN)+ has poor solubility in CaAl2O4 (x ≈ 0.025) and SrAl2O4 lattices (x ≈ 0.045) but a considerable integrated quantity of (SiN)+ against BaAl2O4 (x ≈ 0.6). Because of the low solubility of (SiN)+, incorporation of (SiN)+ barely affects the luminescence characteristics of MAl2O4 when doped with Eu2+ (M = Ca, Sr), resulting in discharges in green as well as blue at nearly constant wavelengths measured at 440 as well as 515 nm, respectively. With certain concentrations of (SiN)+ as well as Eu2+, Eu2+-doped BaAl2−xSixO4−xNx emits one wide green discharge line under a maximum within the region 500 – 526 nm. Furthermore, once we add nitrogen, both the excitation as well as discharge lines for Eu2+ exhibit one substantial redshift. BaAl2−xSixO4−xNx: Eu2+ is a compelling transmuting phosphor that can be utilized for WLED devices because of its efficient stimulation in the range of 390–440 nm radiation.